Initial Studies on Web based Tourism Decision Support System (WBTDSS) Case Study: Langkawi Island, Kedah - Azizul, Ahmad; Tarmiji, Masron; Mohd Azam, Osman; Badaruddin, Mohamed; Azizan, Marzuki (2011)
Geographic (spatial) information technology refers to any technology related to computing, storing and manipulating spatial information and this technology played an important role in many fields today. According to Foresman (1998), about 80 to 90 percent of the collected data has a geographic component (spatial). This is because the spatial data staying in all places and always tied to each record data with each other. This technology has changed the geography discipline by providing capabilities to analyze the whole information whether it's quantitative or qualitative information (Wilbanks, 2004: 12). Although they are many spatial information technology, the main applications that were chosen for this paper are Global Positioning System (GPS), remote sensing, aerial photography and Geographic Information System (GIS). "Visitor" is defined by the World Trade Organization (WTO) for statistical purposes as anyone who makes a visit to a destination other than the destination he lived in a period of not more than a year with a purpose other than to get paid from visit that was carried out. Visitors are divided into two categories: international visitors - visitors who travel to other countries and domestic visitors - visitors who travel in their own country. In the Tourism Industry, GIS is used to provide a digital base map for printed maps, digital files for internet mapping, digital files for mobile mapping, attractions map and website with interactive mapping (Ake, 2004). The methodology this study consisted of five phases; user requirements study, data collection: primary and secondary data, designing and developing geodatabase prototype, designing and developing a web based prototype for tdss testing, and implementation and final results.